2019
DOI: 10.1186/s12974-019-1482-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma VCAM1 levels correlate with disease severity in Parkinson’s disease

Abstract: Background Parkinson’s disease (PD) is a progressive neurodegenerative disease characterized by motor and non-motor symptoms. There is increasing evidence that PD pathology is accompanied by an inflammatory response. This is highly relevant for understanding disease progression and the development of novel neuroprotective therapies. Objective Assessing potential dysregulation of a panel of inflammatory mediators in the peripheral blood mononuclear cells (PBMCs) and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…Moreover, they can be found in acute disseminated encephalomyelitis, which is a postinfectious inflammatory disease, and in the serum and cerebrospinal fluid (CSF) of patients with multiple sclerosis, where their level correlates with disease severity (70). Similar observations were made in patients suffering from Parkinson's disease (71), highlighting the potential relation between sCAM levels in biological fluids and inflammation. Interestingly, an increase in soluble VCAM-1 has been detected in severe DENV infections and was proposed to represent a marker to monitor disease severity (72).…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, they can be found in acute disseminated encephalomyelitis, which is a postinfectious inflammatory disease, and in the serum and cerebrospinal fluid (CSF) of patients with multiple sclerosis, where their level correlates with disease severity (70). Similar observations were made in patients suffering from Parkinson's disease (71), highlighting the potential relation between sCAM levels in biological fluids and inflammation. Interestingly, an increase in soluble VCAM-1 has been detected in severe DENV infections and was proposed to represent a marker to monitor disease severity (72).…”
Section: Discussionmentioning
confidence: 67%
“…Under these conditions, they contribute to the recruitment of circulating blood cells into the brain microvasculature via the expression of adhesion molecules [ 79 ]. Interestingly, high levels of soluble VCAM1 were reported in plasma from PD patients when compared to age-matched controls, that correlated with disease stage and motor impairment [ 81 ], indicating strong blood–brain connections through cell traffic.…”
Section: Endothelial Inflammation and Blood–brain Barrier Permeabimentioning
confidence: 99%
“…Furthermore, evidence that vascular inflammation, marked by increased endothelial expression of vascular cell adhesion molecule VCAM1, stokes CNS aging by decreasing neural stem cell number and increasing microglial reactivity has been reported (11). Elevated levels of VCAM1 have also been found to correlate with Parkinson's disease severity (12) and, recently, lymphocytes known to bind VCAM1 in brain vasculature were found in aged and AD patient brains (13,14). Single-cell transcriptomic analysis of hippocampal brain endothelial cells (BECs) has shown that age-related changes in these cells are rooted in responses to innate inflammatory cues, hypoxic stimuli, and oxidative stress (15).…”
Section: Introductionmentioning
confidence: 99%